ASSESSMENT OF ATHEROSCLEROSIS IN PATIENTS WITH OSTEOARTHRITIS USING VASCULAR DOPPLER ULTRASOUND (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article analyzes the characteristics of atherosclerosis development in patients with osteoarthritis and the possibilities for its early detection using vascular Doppler ultrasound. According to contemporary scientific data, osteoarthritis is no longer considered solely a degenerative joint disease but is increasingly recognized as a systemic pathology associated with chronic low-grade inflammation. These inflammatory processes contribute to the development of atherosclerosis through endothelial dysfunction, disturbances in lipid metabolism, and metabolic alterations. The study examines the pathogenetic relationship between osteoarthritis and atherosclerosis, as well as key cardiovascular risk factors. The diagnostic value of vascular Doppler ultrasound in detecting subclinical atherosclerosis is highlighted, including its principal indicators such as intima–media thickness, atherosclerotic plaques, and hemodynamic changes. Analysis of current studies indicates that increased intima–media thickness, vascular structural alterations, and impaired blood flow are frequently observed in patients with osteoarthritis. Additionally, age, inflammation, dyslipidemia, and physical inactivity are identified as significant contributors to cardiovascular risk formation. The noninvasive, safe, and highly informative nature of Doppler ultrasonography supports its widespread application in clinical practice. The use of pie charts in the article allows for a clear visualization of the relative contribution of various factors. In conclusion, early detection and prevention of atherosclerosis in patients with osteoarthritis play a crucial role in reducing cardiovascular complications.